Giving up or Pursuing Translation? The Impact of Strategic Competence on Motivational Persistence - Ayşe Işık Akdağ (Selçuk Üniversitesi Edebiyat Fakültesi Dergisi, 2020)
This study aims to analyse the strategic competence that Translation Studies students develop during the translator training process according to some variables and to explore its impact on the pursuit of translation goals. Research data was collected using the Metacognitive Learning Scale developed by Namlu (2004) and the Motivational Persistence Scale adapted into Turkish by Saricam et al. (2014). Research is conducted with 214 students enrolled in the English, French and German departments of Translation Studies in a public university using the relational screening model and correlational survey method. Results show that trainee translator’s strategic competence does not vary by department or class but by gender, age and academic achievement. General strategic competence and planning strategies of female translator candidates were higher than males and students’ strategic competence mean is slightly above the average. Another result was that when strategic competence increases, motivational perseverance increases accordingly. Furthermore, students using planning strategies or organizational strategies are more likely to pursue current and distant translation goals. Students using supervision or evaluation strategies on the other hand, can return to unresolved past goals in addition to going after current and long-term translation goals.